Optimal control of a small fixed-wing UAV about concatenated trajectories. (July 2015) - Arifianto, Ony; Farhood, Mazen
Abstract: The paper focuses on the control of a small fixed-wing unmanned aerial vehicle (UAV) along trajectories. The trajectories are generated in real-time from a library of pre-specified motion primitives. Two concatenated primitive trajectories are considered: one formed from seven primitives and exhibiting a figure-8 geometric path and another composed of a Split-S maneuver that settles into a level-turn trim trajectory. Switched control systems stemming from ℓ 2 -induced norm synthesis approaches are designed for discrete-time linearized models of the nonlinear UAV system. These controllers are analyzed based on simulations in a realistic operational environment and are further implemented on the physical UAV. Abstract : Highlights: Trajectory tracking controllers are designed for and executed on a fixed-wing UAV. Trajectories are generated online by concatenating pre-specified motion primitives. Switched controllers are designed for discrete-time linearized models of the UAV. LMI-based control approaches with H -infinity type performance are applied. Lemniscate and aerobatic trajectories are used to validate designed controllers.